Long-term Survival in a Child with Malignant Insulinoma After Liver Transplantation - Elzbieta Moszczynska; Arnika Wydra; Klaudia Zasada; Marta Baszynska-wilk; Dorota Majak; Anna Sliwinska; Wieslawa Grajkowska (Galenos Yayincilik, 2024)
Insulinoma is one of the pancreatic neuroendocrine tumors (PanNET) and is exceptionally rare in children. The tumor leads to severe hypoglycemia caused by excessive insulin release. We report a pediatric patient with malignant insulinoma who underwent liver transplantation (LT) due to liver metastases of the insulinoma. A 13-year-old girl presented with symptoms of hypoglycemia due to hyperinsulinism. On computed tomography (CT), a polycystic lesion in the head of the pancreas and enlarged lymph nodes were revealed. A modified Whipple's operation was performed, and histological examination confirmed PanNET. CT also showed an enlarged liver with numerous metastases. Allogeneic LT was carried out successfully. Positron emission tomography-CT using 68Ga-DOTA-labeled somatostatin analogs (SSAs) at the age of 22 years confirmed complete metabolic remission. The patient currently remains under immunosuppressive and anti-proliferative treatment. Multiple surgical interventions, LT combined with SSAs, and immunosuppressive medication proved effective in this case of metastatic malignant insulinoma.